Perception of the safety of a place by the urban and rural population in Slovenia - Černič Istenič, Majda (Revija za kriminalistiko in kriminologijo, 2021)
Statistics on the incidence of crime in rural and urban areas around the world do not present a consistent picture and reveal the problem of the dark figure of crime, which raises at least two questions: 1) whether there is indeed a difference between urban and rural areas in the incidence and prevalence of crime; and, if so, 2) what characteristics of these places are believed to influence the incidence of crime. The aim of this article is to answer these two questions by examining people’s beliefs (social constructs) theoretically and empirically using Slovenia as an example. The data used for this purpose are based on 60 structured interviews with urban and rural residents of both genders, aged 18 years and older, conducted throughout Slovenia in the winter of 2016–2017. The results point to the presence of strong myths about crime as a phenomenon of (larger) cities in Slovenia, and at the same time to the perceived lower quality of life in rural areas compared to cities. The idealised image of a safe countryside held by inhabitants of both rural and urban areas is confirmed by the well-known construction of the countryside as the “other” that supports the social hegemony of cities over the countryside in the accumulation of its space, human and natural resources. The paper concludes that the issue of inadequate reporting on crime in the context of rural and urban places needs further research and suggests that the influence of the media on the production and reporting of images of crime in specific places should be examined in more detail.
Keywords: kazniva dejanja; Kriminal; kriminaliteta; mesta; Podeželje; zaznavanje varnosti